A universal glycoenzyme biosynthesis pipeline that enables efficient cell-free remodeling of glycans - Thapakorn Jaroentomeechai; Yong Hyun Kwon; Yiwen Liu; Olivia Young; Ruchika Bhawal; Joshua D. Wilson; Mingji Li; Digantkumar G. Chapla; Kelley W. Moremen; Michael C. Jewett; Dario Mizrachi; Matthew P. DeLisa (Nature Communications, 2022)
Access to glycoenzymes for basic and applied research is limited by difficulties with their recombinant expression. Here, the authors describe a universal strategy for converting membrane-bound glycosyltransferases into water-soluble biocatalysts, which are expressed at high levels with retention of activity.